ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING THROUGH POWER POINT MEDIA ON STUDENTS OF SMAN 5 PONTIANAK - Rianawati Rianawati; Sumar’ih Sumar’ih; Yapandi Ramli; Khairawati Khairawati (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
PAI subjects seem monotonous, stiff, and unattractive due to the lack of mastery of Islamic Religious Education teachers in using PowerPoint media. This study was used as a qualitative method with data collection techniques through interviews and observations. Data analysis was used data reduction, data display, and data verification techniques. Data validation did by using member checking techniques, data triangulation, and extending the observation period. The informants were 3 PAI teachers. Research focus: 1) How was the PowerPoint display design in Islamic Religious Education learning? 2) How were Islamic Religious Education learning activities using PowerPoint media? The objectives of this research were: 1) To describe the PowerPoint display design in Islamic Religious Education learning. 2) To describe Islamic Religious Education learning activities using PowerPoint media. The findings of this study were 1) The display of the PowerPoint design was not good in every aspect, and the appearance of solid material, images, colors, and films did not match the material. 2) PAI learning activities were less conducive, active, and creative because students were not comprehending enoughand less able to explain the material.